SOIL CHARACTERISTICS AND BEARING CAPACITY USING DYNAMIC CONE PENETROMETER (DCP) TEST IN SOUTH BARITO REGENCY - Frans Putra Genesa; Nathanael Yanuar Kristianto; Lola Cassiophea; Muhtadin; Gagas Wira Syahputra (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2025)
This research analyzes soil characteristics and bearing capacity based on Dynamic Cone Penetrometer (DCP) testing in South Barito Regency. The study aims to evaluate the relationship between penetration depth, number of blows (N-Blows), and soil bearing capacity (Qall) and to identify suitable soil layers for foundation planning. Testing was conducted at various locations with depths up to 100 cm, including 10 cm intervals. The results show that shallow layers (0–10 cm) have low bearing capacity due to heterogeneous soil properties, while intermediate to deeper layers (40–100 cm) exhibit increased strength and soil stability. Regression analysis revealed high R² values for most locations, such as 0.999 at DCP-17, indicating an almost perfect relationship between the variables. Based on these findings, shallow foundations are recommended for locations with high bearing capacity, while deep foundations are advised for soils with high heterogeneity. This research provides a significant contribution to supporting safe and efficient infrastructure design in the South Barito region.